Ethnomathematics of Samin Tribe's Culture: An Approach to Instructional Mathematics Learning - Novianti, Dwi Erna; Zaenuri, Zaenuri; Wardono, Wardono; Sugiman, Sugiman (Jurnal Pendidikan Progresif, 2025)
Ethnomathematics of Samin Tribe's Culture: An Approach to Instructional Mathematics Learning. Objectives: This study aims to explore the ethno-mathematics of the Samin tribes’ culture that is applied in the form of mathematics instrumental questions on data analysis and probability materials in statistics. Method: This research applied a qualitative research design of an ethnographic approach. Ethnography is an approach that utilizes various data collection techniques, such as observation and interviews, which are complemented by the direct involvement of the researchers to gain a deep understanding of their participants. The data collection techniques used were direct observation and in-depth interviews. Data analysis was carried out qualitatively through three main stages, namely data reduction, data presentation, and drawing conclusions. The data presented are the results of observations related to the Samin tribe culture, which are then analyzed for the mathematical elements contained in the culture to be presented in the form of an instrumental question. Findings: The results of the exploration of ethnomathematics in the Samin tribe revealed cultural elements in the form of objects and non-objects. The Object elements are in the form of gamelan, udheng samin, and batik samin. While non-object elements are cultural practices in the form of the tradition of “Petung”. The corresponding forms of mathematical connections are mathematical concepts related to geometry, algebra, statistics, probability, combinations, and permutations. Conclusion: Based on the results of the exploration, a set of questions related to the Samin tribes’ culture was produced on the topic of Data analysis and Probability (statistics) for junior high school students. These questions can be applied or implemented in the mathematics learning process, so that mathematics learning based on this culture adds another value of knowledge for the students, instead of mathematics itself. The results of this research are in the form of question prototypes that potential to be developed and validated further, thus can be applied in the learning process. Keywords: ethnomathematics, samin tribe, question prototypes, mathematics learning.